Omar Khayyam - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Chin, Mei Lee; Siti Aisah, Harun; Norhayati, Nordin; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras; Nurul Nadia, Abd Razak (Penerbit UMP, 2011)
Omar Khayyam (104B-1131) was a Persian polymath: philosopher, mathematician, astronomer and poet. He also wrote treatises on mechanics, geography, mineralogy, music, climatology and theology. He was born In Nlshapur,(modern-day Iran), then a Seljuq capital In Khorasan, which rivaled Cairo or Baghdad In cultural prominence In that era.